Autoantigen TRIM21/Ro52 as a Possible Target for Treatment of Systemic Lupus Erythematosus. (4th June 2012) - Yoshimi, Ryusuke; Ishigatsubo, Yoshiaki; Ozato, Keiko
Abstract : Systemic lupus erythematosus (SLE) is a chronic, systemic, and autoimmune disease, whose etiology is still unknown. Although there has been progress in the treatment of SLE through the use of glucocorticoid and immunosuppressive drugs, these drugs have limited efficacy and pose significant risks of toxicity. Moreover, prognosis of patients with SLE has remained difficult to assess. TRIM21/Ro52/SS-A1, a 52-kDa protein, is an autoantigen recognized by antibodies in sera of patients with SLE and Sjögren's syndrome (SS), another systemic autoimmune disease, and anti-TRIM21 antibodies have been used as a diagnostic marker for decades. TRIM21 belongs to the tripartite motif-containing (TRIM) super family, which has been found to play important roles in innate and acquired immunity. Recently, TRIM21 has been shown to be involved in both physiological immune responses and pathological autoimmune processes. For example, TRIM21 ubiquitylates proteins of the interferon-regulatory factor (IRF) family and regulates type I interferon and proinflammatory cytokines. In this paper, we summarize molecular features of TRIM21 revealed so far and discuss its potential as an attractive therapeutic target for SLE.